Analysis of the Effect of Boro River Backwater as an Impact of Flood Inundation in Sewu Urban Village, Surakarta City - Amina, Syakira; Hadiani, Rr.; Solichin (Indonesian Journal Publisher, 2025)
Backwater is a condition where the flow of river water is obstructed, causing the water level to rise and overflow into the surrounding area. The backwater phenomenon is the main cause of flood inundation in Sewu Village. The confluence of two rivers, namely the main Bengawan Solo River and the Boro River, causes the flow of water from the Boro River to be obstructed due to the higher elevation of the River in the Bengawan Solo River. Therefore, this study aims to analyze the effect of the Boro River backwater on flood inundation in Sewu Village with a 20-year (Q20), 25-year (Q25), and 50-year (Q50) return period flood discharge using the Soil Conservation Service synthetic unit hydrograph method with HEC-HMS software. This research uses hydraulic simulation by simulating river flow to find out the location of backwater that causes runoff. The results showed that the 20-year return period flood discharge (Q20) of 12.3 m³/s, 25-year return period (Q25) of 12.8 m³/s, and 50-year return period (Q50) of 14.4 m³/s significantly affected the water level in Boro River, which resulted in an increase in the flood inundation area in Sewu Village. Hydraulic simulations revealed that the critical point of backwater in Boro River affects the maximum water depth of the river, such as the 20-year return period (Q20) has an increase difference of 0.40 meters, the 25-year return period (Q25) of 0.32 meters, and the 50-year return period (Q50) of 0.45 meters.